2016
DOI: 10.12968/ajmw.2016.10.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of pain management among nurses in labour wards in Ibadan, Nigeria

Abstract: Background: It is not clear whether awareness of pain management has influenced the management of labour pain by nurse/midwives in Ibadan, Nigeria. Many women in labour do not get optimal pain relief, despite awareness of the importance of pain management. Aims: This study aimed to assess knowledge and practice of labour pain management among nurse/midwives in Ibadan. Methods: This cross-sectional study included 87 nurse/midwives on duty in labour rooms of three hospitals in Ibadan, Nigeria. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
7
2
3
Order By: Relevance
“…In our study, most of the respondents had a good knowledge level, which is in line with the report by Ogboli-Nwasor, in which 94.8% of respondents in their study population agreed that pain relief is needed during labour 9 , and by Ojerinde et al in which more than two-thirds of the respondents were knowledgeable about management of pain in labour 25 . However, this is unconnected with the quality of training of respondents in the study population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, most of the respondents had a good knowledge level, which is in line with the report by Ogboli-Nwasor, in which 94.8% of respondents in their study population agreed that pain relief is needed during labour 9 , and by Ojerinde et al in which more than two-thirds of the respondents were knowledgeable about management of pain in labour 25 . However, this is unconnected with the quality of training of respondents in the study population.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, Sahile et al 31 stated that professional qualifications were significantly associated with the practice of non-pharmacological labour-pain management methods, and skilled attendants with higher qualifications were 2.87 times more likely to use labour-pain management methods than those who had low level qualifications. Knowledge was seen as an important factor affecting the quality of care and ultimately pain relief and fulfilment in care 25 . It has been stated that the education of skilled attendants can improve the management of labour pain and use of labour pain relief methods 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that 45.8% of obstetric caregivers had inadequate knowledge about labour pain relief methods. Our finding is lower than the findings reported from Tigray, Ethiopia (60.1%) and Ibadan, Nigeria (66.7%), respectively [13,17]. This difference might be explained in terms of difference in study setting and socio-demographic characteristics of study participants.…”
Section: Knowledge Of Obstetric Caregivers Towards Labour Pain Reliefcontrasting
confidence: 90%
“…In this study, systemic opioid (Pethdine) was reportedly one of the most identified pharmacological pain relief methods, which is similar with studies from Zaria, Greek, and Ibadan (Nigeria), respectively [6,16,17]. This might be due to accessibility and low cost of the drug on the market.…”
Section: Knowledge Of Obstetric Caregivers Towards Labour Pain Reliefsupporting
confidence: 81%
See 1 more Smart Citation